Taijin Kyofusho and Social Anxiety and Their Clinical Relevance in Indonesia and Switzerland - Vriends, Noortje; Pfaltz, Monique C.; Novianti, Peppy; Hadiyono, Johana (Frontiers in Psychology, 2013)
Background: Taijin Kyofusho (TKS) is an interpersonal fear to offend others and is defined by DSM-IV as a culturally bound syndrome that occurs in Japan and Korea. Recently, cases with TKS have also been recognized in other cultures. The present questionnaire study investigated self-report TKS symptoms and social anxiety symptoms, and their clinical relevance in an Indonesian and Swiss sample. It also investigated if self-construal is associated with TKS and social anxiety, and if self-construal is a mediator of the expected association between cultural background and social anxiety and TKS symptoms. Method: 311 Indonesian and 349 Swiss university students filled out the Liebowitz Social Anxiety Scale, the Taijin Kyofusho Scale, the Self-Construal Scale, self-report social phobia DSM-IV criteria, and rated their wish for professional help to deal with social fears. Results: TKS and social anxiety symptoms were higher in the Indonesian than the Swiss sample. TKS symptoms were associated with clinical relevance in Indonesia, whereas in Switzerland only social anxiety symptoms were associated with clinical relevance. Independent self-construal was negatively associated and interdependent self-construal was positively associated with TKS and social anxiety symptoms. Interdependent self-construal mediated the association between cultural background and these symptoms. Discussion: TKS might be a clinically relevant syndrome in all individuals or cultures with an interdependent self-construal or less independent self-construal. The proposal to include the fear of offending others in the DSM-V criteria of social phobia is supported by the present findings.